Efficacy and Safety of Dalbavancin for the Treatment of Acute Bacterial Skin and Skin Structure Infection (ABSSSI) in Patients with Diabetes Mellitus. (4th October 2017) - Nowak, Michael; Rappo, Urania; Gonzalez, Pedro L; Chen, Jie; McGregor, Jennifer S; Bryowsky, Jason; Talan, David
Abstract: Background: ABSSSIs are common in patients with diabetes and have an increased risk of complications. Dalbavancin is a long-acting lipoglycopeptide with potent activity against Gram-positive pathogens responsible for ABSSSI, including methicillin-resistant Staphylococcus aureus (MRSA), and has demonstrated activity in ABSSSI with single-dose administration. We assessed outcomes in patients with and without diabetes in a clinical trial evaluating the efficacy of dalbavancin for ABSSSI. Methods: In a double-blind, phase 3 trial, adult patients with ABSSSI involving deeper soft tissue or requiring significant surgical intervention, defined as major abscess, cellulitis, and traumatic wound/surgical site infection were randomized 1:1 to dalbavancin as a single-dose (1500 mg) or as a two-dose regimen (1000 mg on Day 1 and 500 mg on Day 8). The primary endpoint was ≥20% reduction in erythema at 48–72 hours; clinical success on Days 14 and 28 was defined as improvement in lesion size and signs and symptoms. P -values were obtained using Fisher's exact test for categorical variables and Wilcoxon rank-sum test for continuous variables. In a post-hoc subgroup analysis, outcomes were compared among the subgroups of participants with and without diabetes. Results: There were 76/698 (10.9%) participants with diabetes and 622/698 (89.1%) participants without diabetes. Participants with diabetes were more likely to be older or obese, and had higher rates of cellulitis, while participants without diabetes had higher rates of abscess (Figure 1). At Days 14 and 28, clinical success was achieved in ≥84% of participants with diabetes, and investigator assessment of cure was achieved in ≥95% of participants with diabetes (Figure 2). Drug-related adverse events were observed in 7 (9.2%) patients with and 44 (7.1%) participants without diabetes. Conclusion: Dalbavancin has similar rates of clinical response and success for the treatment of ABSSSI in patients with or without diabetes. Disclosures: M. Nowak, Allergan plc: Employee, Salary. U. Rappo, Allergan plc: Employee and Shareholder, Salary. P. L. Gonzalez, Allergan plc: Employee and Shareholder, Salary. J. Chen, Allergan plc: Employee, Salary. J. S. McGregor, Allergan plc: Employee, Salary. J. Bryowsky, Allergan plc: Employee and Shareholder, Salary.